2016
DOI: 10.1080/03079457.2015.1117057
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitroattenuated strain ofHistomonas meleagridisprovides cross-protective immunity in turkeys against heterologous virulent isolates

Abstract: In the current study, cross-protective immunity induced by a well-defined clonal strain of Histomonas meleagridis, attenuated by prolonged in vitro cultivation against different clonal heterologous isolates of the same parasite was investigated. For this purpose, 86 turkey poults were assigned to groups consisting of 9-10 birds. Birds of four groups were vaccinated on their 1st day of life followed by re-vaccination on their 14th day of life when the remaining turkeys were left untreated. The challenge was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The action strategy aimed at countering H. meleagridis infection in poultry flocks mainly entails searching for effective preparations of plant origin and developing a vaccine. As indicated by research findings (29), experimental vaccination using in vitro attenuated H. meleagridis effectively protects turkeys from histomonosis and is safe to use, which recommends it as the most promising means of prevention of histomonosis in poultry for the future. However, numerous publications show that, despite satisfactory in vitro results, phytocompounds fail to produce promising effects in vivo in the fight against this flagellate (1,12,14,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The action strategy aimed at countering H. meleagridis infection in poultry flocks mainly entails searching for effective preparations of plant origin and developing a vaccine. As indicated by research findings (29), experimental vaccination using in vitro attenuated H. meleagridis effectively protects turkeys from histomonosis and is safe to use, which recommends it as the most promising means of prevention of histomonosis in poultry for the future. However, numerous publications show that, despite satisfactory in vitro results, phytocompounds fail to produce promising effects in vivo in the fight against this flagellate (1,12,14,32).…”
Section: Discussionmentioning
confidence: 99%
“…This situation and the fact that biosecurity measures do not always prevent H. meleagridis introduction into a flock, infection (4), or ultimate disease outbreak, have forced a new approach to the problem of histomonosis prevention and treatment. That is why recent research focuses on various areas of disease control from the use of phytocompounds (1,12,31) to administration of vaccines (25,29). The presented study aims to assess the therapeutic and preventive efficacy of phytoncides contained in adiCox SOL PF (AdiFeed, Warsaw, Poland), a feed supplement for poultry, in a clinical case of histomonosis in a parent turkey flock, as well as to determine their effect on selected parameters of bird cell-mediated and humoral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two genotypes of H. meleagridis based on the 18S rRNA gene, genotype 1 and genotype 2, with the latter occurring less frequently [13]. Only slight differences in pathogenicity of different clonal isolates within genotype 1 have recently been observed in an experimental study [27]. In comparison, Tyzzer [28] observed variations in virulence of naturally occurring histomonad strains.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments in adult layers have shown that vaccinated birds can be protected from a severe drop in egg production caused by histomonosis (Liebhart et al, 2013b). Most recently, crossprotection by the mentioned attenuated clonal strain against genetically different isolates of H. meleagridis was demonstrated in turkeys (Sulejmanovic et al, 2016).…”
Section: Investigations On Vaccination Against Histomonosismentioning
confidence: 99%